Hitmen for Hire: Exposing South Africa’s Underworld - Beukes, Tobie (Scientia Militaria - South African Journal of Military Studies, 2019)
This book is based on research about criminal assassinations and organised crime in South Africa, conducted by Shaw and his colleagues at the Centre of Criminology in the Faculty of Law at the University of Cape Town (UCT).